2004
DOI: 10.1097/01.asn.0000113248.59077.76
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Benefits with Sirolimus-Based Therapy after Early Cyclosporine Withdrawal

Abstract: Abstract. Graft function at 6 or 12 mo is positively correlated with renal transplant survival. The 36-mo results of a study that tested whether withdrawing cyclosporine (CsA) from a sirolimus (SRL)-CsA-steroid (ST) regimen would affect renal graft survival are reported. Eligible patients (n ϭ 430) who were receiving SRL-CsA-ST were randomly assigned at 3 mo to remain on SRL-CsA-ST or to have CsA withdrawn (SRL-ST group). At 36 mo, the calculated GFR was significantly better with SRL-ST (47.3 versus 59.4 ml/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
148
2
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(166 citation statements)
references
References 20 publications
10
148
2
6
Order By: Relevance
“…As we have described in the initial (12) and subsequent reports (13)(14)(15)(16), this study has shown that early CsA withdrawal has resulted in lower BP, better renal function, and improved graft survival along with improved graft structure and better quality-of-life indices. We report the 5-yr malignancy data from this study and place these findings in perspective with regard to the problem of malignancy in transplant recipients.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…As we have described in the initial (12) and subsequent reports (13)(14)(15)(16), this study has shown that early CsA withdrawal has resulted in lower BP, better renal function, and improved graft survival along with improved graft structure and better quality-of-life indices. We report the 5-yr malignancy data from this study and place these findings in perspective with regard to the problem of malignancy in transplant recipients.…”
mentioning
confidence: 65%
“…A total of 94.5% of the recipients were of white ethnic origin, reflecting the ethnic composition of countries in which the trial was conducted. On the basis of the month 36 and cumulative data available at that time (13), the protocol was amended to discontinue protocol-assigned treatment in the SRL-CsA-ST group. This amendment began affecting the discontinuation rate beginning at the month 48 visit.…”
Section: Methodsmentioning
confidence: 99%
“…62 In addition, sirolimus appears to be associated with a lower risk of developing and successful treatment of post-transplant malignancies including PTLD, skin carcinomas and Karposi's sarcoma. [63][64][65][66][67][68] These results suggest that sirolimus may minimize the risk of developing post-transplant malignancies while maintaining organ transplant viability and may be used to continue immunosuppression and inhibit malignancies recurrence in successfully treated patients.…”
Section: Clinical Activity Of Sirolimus and Derivativesmentioning
confidence: 92%
“…Options include reduction in corticosteroids, 17 substituting tacrolimus for cyclosporine, 18 reducing CNI doses by adding mycophenolate mofetil (MMF), 19 or converting to sirolimus-based immunosuppression. 20 These decisions should be made with the transplant hepatologist involved.…”
Section: Hypertensionmentioning
confidence: 99%
“…33 In cases of diabetes that is poorly controlled despite aggressive medical management, the transplant hepatologist may consider withdrawing corticosteroids or possibly adding MMF to reduce CNI or mTOR inhibitor doses. 20 Switching from tacrolimus to cyclosporine has not been reliably effective in reducing glucose levels and has the cost of worse hypertension and dyslipidemia. 18,34 Dyslipidemia Dyslipidemia is unusual in patients with cirrhosis, which usually results in marked decline in cholesterol levels due to impaired hepatic synthesis.…”
Section: Article Highlightsmentioning
confidence: 99%